The Effectiveness Of English Pronunciation Application For Students’ Motivation In Learning (Conference on English Language Teaching, 2024)
The objective of the research is was to know the influence of applications that consisting pronunciation practices for English language to motivate students for learning pronunciation. This research using experimental research on the participants by using treatment and test which using pre-test and post-test. This research conducted at UIN Prof. K. H. Saifuddin Zuhri Purwokerto. For this research, the sample of research is 3rd semesster students in English Education Program. The convenience sampling was used for the sampling technique. In the research itself, there are 30 participants who divided into two different groups; experimental and control group. Researchers using T-paired Test and N-Gain Score test for analyzing the data of the research which shown the effectiveness of English pronunciation application for students in mmotivation.